Credit Booms-Is China Different? - Chen, Sally; Kang, Joong (Washington, D.C. : International Monetary Fund, 2018)
Strong Chinese output growth after the Global Financial Crisis was supported by booming credit. This credit boom carries risks. International experience suggests that China's credit growth is on a dangerous trajectory, with increasing risks of a disruptive adjustment and/or a marked growth slowdown. Several China-specific factors-high savings, current account surplus, small external debt, and various policy buffers-can help mitigate near-term risks of a disruptive adjustment and buy time to address risks. But, if the risks are left unaddressed, these mitigating factors will likely not eliminate the eventual adjustment, but make the boom larger and last longer. Hence, decisive policy action is needed to deflate the credit boom safely.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet